Using modeling and simulation for scheduling of test cell in an electronic company - Cheng, Yau Tong. (2009)
The primary objective of scheduling is to enable a company to deliver quality parts to the customer on time. However, there are many conflicting factors, both internal and external, that affect the drive to reach this objective. It is almost impossible to deliver quality parts to all the customers on time at all times while maintaining maximum machine utilization and minimum inventory. The management will have to weigh between urgent parts and normal parts; between clearing deliquent line items and meeting due-date of current parts; between major customers and minor customers.